Ratio of lysine to essential amino acids in the diet of guinea pigs (Cavia porcellus) - Castillo Soto, Wilson Lino; Rojas Paredes, Marco Antonio; González Puetate, Iván; Cushicóndor-Collaguazo, Diego Martín (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2022)
The research objective was to evaluate diets with increased levels of total lysine for improved guinea pigs, maintaining the same ratio Lysine: Essential Amino Acids in all diets, on productive and economic parameters from the initial, growing, and finishing phases in guinea pigs. This work was performed at Private University Antenor Orrego - Peru. Twentyfive 15-day-old male guinea pigs with an average weight of 229,57 ± 3,54 g were used. Diets were formulated according to requirements established as treatments, based on Lysine: Amino Acids ratios, variables evaluated in each phase were: daily weight gain (GPD), daily consumption (CD) and feed conversion (CA). A complete randomized design with five treatments and ten replications was used, analysis of variance and Tukey test at 5% were also performed, data were processed with the statistical program JASP Team (2022). Results showed that initial weight, daily weight gain, daily feed intake and feed conversion showed no significant statistical difference in each studied phase; economic benefit was favored by lower dietary lysine levels because of lower feed costs and efficient use of nutrients.
Keywords: Amino acids; guinea pigs; weight gain; feed conversion